2022
DOI: 10.1038/s41598-022-11307-4
|View full text |Cite
|
Sign up to set email alerts
|

Seed priming with selenium and zinc nanoparticles modifies germination, growth, and yield of direct-seeded rice (Oryza sativa L.)

Abstract: Direct-seeded rice (DSR) seeds are often exposed to multiple environmental stresses in the field, leading to poor emergence, growth and productivity. Appropriate seed priming agents may help to overcome these challenges by ensuring uniform seed germination, and better seedling stand establishment. To examine the effectiveness of sodium selenite (Na-selenite), sodium selenate (Na-selenate), zinc oxide nanoparticles (ZnO-NPs), and their combinations as priming agents for DSR seeds, a controlled pot experiment fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 83 publications
(67 reference statements)
2
13
0
Order By: Relevance
“…In 2021, Sharma et al used ZnO NPs prepared from a Senna occidentalis leaf as a nano-initiator to pre-treat seeds of an early flowering pure mutant to improve rice seed germination, seedling vigor, and zinc content in seedlings [ 77 ] ( Figure 9 a). Adhikary et al adopted the idea and used ZnO NPs and selenium as initiators for rice seeds [ 78 ], which enhanced seed vigor and improved conditions such as poor seedling emergence triggered by direct sowing practiced for rice cultivation in South Asia. In addition, Elshayb et al sprayed ZnO NPs on rice with biochar (BC) as a soil amendment.…”
Section: Effect Of Monps On the Growth Of Ricementioning
confidence: 99%
“…In 2021, Sharma et al used ZnO NPs prepared from a Senna occidentalis leaf as a nano-initiator to pre-treat seeds of an early flowering pure mutant to improve rice seed germination, seedling vigor, and zinc content in seedlings [ 77 ] ( Figure 9 a). Adhikary et al adopted the idea and used ZnO NPs and selenium as initiators for rice seeds [ 78 ], which enhanced seed vigor and improved conditions such as poor seedling emergence triggered by direct sowing practiced for rice cultivation in South Asia. In addition, Elshayb et al sprayed ZnO NPs on rice with biochar (BC) as a soil amendment.…”
Section: Effect Of Monps On the Growth Of Ricementioning
confidence: 99%
“…Moreover, priming can be applied to various organs and at various stages of the plant life cycle. The most frequently used is seed priming, which provides faster and more uniform seed germination, ensures efficient nutrient and water uptake, releases photo- and thermo- dormancy, as well as improves seedling vigor in relation to their further growth and yield under both optimal and adverse conditions [ 82 , 83 , 84 ]. Less often, priming concerns seedlings, young plants, or their parts although they show significantly greater tolerance to different abiotic stresses than untreated ones [ 85 , 86 ].…”
Section: Chemical and Physical Agents For Enhancing Plant Resistance ...mentioning
confidence: 99%
“…Additionally, the use of nanopriming had a positive effect on redox homeostasis in wheat plants [ 103 ]. ZnO nanoparticles, sodium selenite (Na-selenite), sodium selenate (Na-selenate), and their combinations as priming agents for direct-seeded rice seeds were also investigated [ 84 ]. It was observed that all tested combinations of the priming agents (10 µmol ZnO-NPs; 50 µmol Na-selenite; 50 µmol Na-selenate; and the following combinations at the mentioned concentrations: Na-selenite + Na-selenate; ZnO-NPs + Na-selenite; ZnO-NPs + Na-selenate; ZnO-NPs + Na-selenite + Na-selenate) resulted in the early emergence of seedlings with increased vigor compared to the control.…”
Section: Chemical and Physical Agents For Enhancing Plant Resistance ...mentioning
confidence: 99%
See 1 more Smart Citation
“…This increases in population may enhance food demand [1,2]. Continuously growing human population and changes in climate due to global warming may affect the prevailing farming practices, reducing crop production [2,3]. Currently, one-third of world agricultural lands suffer from salinization due to inappropriate agrochemical and Agriculture 2022, 12, 1014 2 of 21 agriculture practices, and industrial pollution also exacerbates this problem [4,5].…”
Section: Introductionmentioning
confidence: 99%